EFEKTIVITAS PROGRAM DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SMP SARI BUANA MAKASSAR - Harun Sally, Jihan Safira Rospitasari; Nur, Andi Cudai; Niswaty, Risma (Patria Artha Journal of Accounting dan Financial Reporting, 2025)
This study aims to evaluate the effectiveness of the School Operational Assistance (BOS) Fund Program at SMP Sari Buana Makassar by referring to five effectiveness indicators proposed by Campbell J.P. and by assessing its implementation in accordance with the BOS guideline regulations. The research employs a qualitative method with data collected through observations, in-depth interviews, and documentation. The findings reveal that the BOS Fund Program at SMP Sari Buana Makassar is generally effective in several aspects, particularly in fund allocation, performance measurement, quality of education, and participation of the school committee. However, certain areas still require improvement in fund utilization and monitoring mechanisms. Overall, the study provides a comprehensive overview of how effectively the BOS Fund Program supports school operational activities based on Campbell J.P.’s concept and the official BOS guidelines.